Two remakable new species of Notocera Amyot and Serville, 1843 (Hemiptera, Membracidae, Hypsoprorini) from the Brazilian Caatinga - Creão-Duarte, Antônio José; Rothéa, Rembrandt Romano Andrade Dantas; Lourenço, Aline; Cabral, Valberta Alves; Evangelista, Olivia (Zootaxa, 2017)
In this paper, two remarkable new species of Notocera Amyot & Serville from the Brazilian Caatinga are described: N. colavitei Creão-Duarte and Róthea sp. nov. and N. sakakibarai Creão-Duarte and Lourenço sp. nov. Illustrations are presented for adult habitus and taxonomically relevant characters, which are briefly discussed. In celebration of Dr. Sakaki-bara’s oustanding career, photographs of the holotype of N. camelina Sakakibara, 1977 are provided, along with reproductions of his outstanding artwork featured in the original description of this species.